Effect Of Compaction Pressure And Addition Of Silicon On Microstructure And Compressive Properties Of Porous Magnesium - Ooi, Lhaang Chee (Universiti Sains Malaysia, 2018)
Porous Magnesium has been recognized as a promising structural material for automotive and aerospace industry due to light-weight which leads to highly fuel-efficient design. The experiment was divided into two parts. In the first part, porous Mg wasfabricated by powder metallurgy using Poly(Methyl Methacrylate) (PMMA) as a space holder. Compaction pressure was varied from 200, 250, 300, 350 to 400 MPa. The green body was sintered using double sintering profile at temperature of 620°C. The porous Mg fabricated was then characterized for morphology, porosity, density, phases, compressive strength and energy absorption properties. Density of porous Mg increases, and the porosity decreases with increasing compaction pressure. The mechanical characterization indicated that porous Mg compacted at 400 MPa exhibited the highest compressive strength, compressive yield stresss and showed the most optimum ideal energy absorption efficiency. For second part, effect of addition silicon to porous Mg was studied. Mg, Si and PMMA powders are mixed in ratio of 78:2:20, 76:4:20, 74:6:20, 72:8:20, 70:10:20 and the 65:15:20, compacted at 400 MPa and sintered at 450°C. The compressive yield stress of porous Mg under 400 MPa is 33.65 MPa but the highest compressive yield stress of porous Mg-Si is 36.89 MPa. Porous Mg has the average ideal energy absorption efficiency 1.571 while porous Mg-Si have average ideal energy absorption efficiency of 2.261 at 2 wt.% of silicon. Addition of silicon has significant effect on the properties of porous Mg which increase the compressive yield strength of the porous Mg and ideal energy absorption efficiency.